PENERAPAN KOMUNIKASI EFEKTIF DALAM RUMAH TANGGA MELALUI KONTEN EDUKASI - Muh. Aditiya Ramadhan (SATRIA BHAKTI, 2026)
A harmonious family life depends heavily on a couple's ability to communicate. Unfortunately, many couples find it difficult to maintain healthy interactions, so that small problems often escalate into conflicts that lead to divorce. In Indonesia, the divorce rate continues to rise each year, a phenomenon that underscores the importance of concrete efforts to strengthen communication skills within the household. This initiative takes the form of educational videos on healthy communication patterns, which are then distributed via the Instagram platform. Through this community service activity, it is hoped that the public will gain a deeper understanding of how to build open, empathetic, and supportive communication within the household. The implementation of this activity is expected to help reduce the potential for conflict and provide couples with the tools to maintain household harmony, while also serving as a reference for individuals preparing for marriage.